If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-2(x+21)=20+5x-(-8)
We move all terms to the left:
3x-2(x+21)-(20+5x-(-8))=0
We multiply parentheses
3x-2x-(20+5x-(-8))-42=0
We calculate terms in parentheses: -(20+5x-(-8)), so:We add all the numbers together, and all the variables
20+5x-(-8)
determiningTheFunctionDomain 5x+20-(-8)
We add all the numbers together, and all the variables
5x+28
Back to the equation:
-(5x+28)
x-(5x+28)-42=0
We get rid of parentheses
x-5x-28-42=0
We add all the numbers together, and all the variables
-4x-70=0
We move all terms containing x to the left, all other terms to the right
-4x=70
x=70/-4
x=-17+1/2
| -51=7-(-5+9r | | 3n+3=45 | | 4(y-15)=4 | | h/2−2=1 | | 7(3x-4=21x-28 | | 6x+7=-9x+127 | | 2^(x^2)×2^4=32 | | X/6-4=x/5 | | 58=g/8+50 | | 3x+24=7x-13 | | 16-3ss=5 | | 11/15=55/x | | 9x-17=-7+9x | | h/2− 2=1 | | 4x-9x-11=-5x+8-11 | | 7-(-5+9)r=-51 | | d−7=28 | | 41/4c=2 | | 48=n-46 | | 22+2x=-7(x-8)+2 | | 2x6=2x | | 7=9+2v | | 7x-9-3x=23 | | -1/2r+6=3 | | z/3+ 4=6 | | 5/6x-3-7/6+2=8 | | −7x+8+9x=−2 | | -8x-4=3x-4+4x | | x/7-4x=x/7 | | 60-4x=150+2x | | 144=-3(-8x-8) | | X-9=4x+9x+3 |